2022
DOI: 10.17694/bajece.970685
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring, Analysis and Control of Power Parameters in Residential Houses Using LabVIEW

Abstract: Electrical energy consumed in residential has an important value in total consumption. For this reason, monitoring and control of the electricity consumed in the residential offers a significant potential for energy saving. In this study, the power parameters of the linear and nonlinear loads used in the residential have measured, analyzed and controlled in real time. Thanks to real-time monitoring, analysis and control of power parameters ensure efficient use of energy. For this, power parameters of the loads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These harmonics that periodically occur in a facility can cause equipment malfunction, data distortion, transformer and motor insulation failure, overheating of neutral buses, and solid-state component breakdown [12]. Moreover, according to article [11], this harmonic distortion leads to failure of electrical or electronic components, transformer heating, failure of power factor correction capacitors, and losses in power generation and transmission. In Akagi's study, he showed the minimum and maximum values for the Total Harmonic Distortion (THD) in a typical three-phase power system in Japan with a rating of 6.6kV in power distribution system [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These harmonics that periodically occur in a facility can cause equipment malfunction, data distortion, transformer and motor insulation failure, overheating of neutral buses, and solid-state component breakdown [12]. Moreover, according to article [11], this harmonic distortion leads to failure of electrical or electronic components, transformer heating, failure of power factor correction capacitors, and losses in power generation and transmission. In Akagi's study, he showed the minimum and maximum values for the Total Harmonic Distortion (THD) in a typical three-phase power system in Japan with a rating of 6.6kV in power distribution system [1].…”
Section: Introductionmentioning
confidence: 99%
“…For the individual odd harmonic frequency, THD and must not exceed 3%. Harmonics in the power system are reprimanded for the decrease in the quality of power accessible to non-linear loads [11]. To suppress the effects of power system harmonics, harmonic filters are used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations